IMPACTO AMBIENTAL NAS ÁGUAS SUBTERRÂNEAS DA BACIA HIDROGRÁFICA DO RIO PARDO (SP) - LIXÕES E PESTICIDAS - Sinelli, Osmar; Avelar, Wagner Eustáquio Paiva; Lopes, João Luis Calegari; Rozelli, Marcelo (Águas Subterrâneas, 1988)
Resumo não disponível.